2021
DOI: 10.3389/fnagi.2021.656990
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Disease and Depressive Symptomatology in Individuals With Subjective Cognitive Decline: A Community-Based Study

Abstract: Subjective cognitive decline (SCD) may be the first sign of Alzheimer's disease (AD), but it can also reflect other pathologies such as cerebrovascular disease or conditions like depressive symptomatology. The role of depressive symptomatology in SCD is controversial. We investigated the association between depressive symptomatology, cerebrovascular disease, and SCD. We recruited 225 cognitively unimpaired individuals from a prospective community-based study [mean age (SD) = 54.64 (10.18); age range 35–77 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 73 publications
1
16
2
Order By: Relevance
“…Both the internal capsule and posterior WM tracts receive dense cholinergic input, and increased MD in cholinergic WM pathways was associated with greater cerebrovascular disease and lower cognitive performance in our cohort [ 49 ]. Finally, as we showed in a recent study using the same cohort, the association between the number of subjective cognitive complaints and WM neurodegeneration was independent from depressive symptomatology [ 50 ], despite depressive symptomatology is consistently associated with SCD [ 9 , 12 , 13 ]. All together, these findings indicate that SCD is associated with WM neurodegeneration in certain regions that go beyond age- or depressive symptomatology-related effects.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Both the internal capsule and posterior WM tracts receive dense cholinergic input, and increased MD in cholinergic WM pathways was associated with greater cerebrovascular disease and lower cognitive performance in our cohort [ 49 ]. Finally, as we showed in a recent study using the same cohort, the association between the number of subjective cognitive complaints and WM neurodegeneration was independent from depressive symptomatology [ 50 ], despite depressive symptomatology is consistently associated with SCD [ 9 , 12 , 13 ]. All together, these findings indicate that SCD is associated with WM neurodegeneration in certain regions that go beyond age- or depressive symptomatology-related effects.…”
Section: Discussionsupporting
confidence: 51%
“…Because multiple pathologies usually coexist in the brain of cognitively unimpaired individuals [ 53 , 54 ], future studies should unveil the pathologies underlying non-AD patterns of GM and WM neurodegeneration in SCD. Investigating pathologies such as cerebrovascular disease and tauopathies is warranted due to their contribution to SCD in community-based cohorts [ 11 , 49 , 50 , 55 ]. A limitation of our cohort is that we do not have biomarkers for amyloid-beta and tau-related pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that 34% of the variance in SCC reported during the COVID‐19 pandemic was explained by a combination of perceived stress, negative emotions, and poorer general physical health related to prolonged confinement or quarantine 123 . Certain medical conditions may also be associated with elevated reports of SCC and increased NPS, including migraines and cerebrovascular disease, although the study examining cerebrovascular disease found that NPS were more associated with perceived SCD than cerebrovascular disease itself 124,125 …”
Section: Neuropsychiatric Symptoms In Scdmentioning
confidence: 99%
“…Yet, SCD individuals have shown an increased risk for future cognitive impairment and dementia compared to non-SCD, independent of the origin of the sample (i.e., memory clinic or general population; Slot, Sikkes, Berkhof, Brodaty, van der Flier, et al, 2019 ). Furthermore, SCD has been associated with multiple underlying brain pathological markers, such as increased amyloidosis and tauopathies ( Buckley et al, 2017 ), gray and white matter neurodegeneration ( Cedres et al, 2021 ), and small vessel disease ( Diaz-Galvan, Cedres, et al, 2021 ). In fact, it has been shown that amnestic SCD (i.e., cognitive complaints referring to the memory domain) presents a brain atrophy pattern similar to that typically presented in Alzheimer’s disease (AD; Diaz-Galvan, Ferreira, et al, 2021 ).…”
mentioning
confidence: 99%
“…Furthermore, SCD has been associated with multiple underlying brain pathological markers, such as increased amyloidosis and tauopathies ( Buckley et al, 2017 ), gray and white matter neurodegeneration ( Cedres et al, 2021 ), and small vessel disease ( Diaz-Galvan, Cedres, et al, 2021 ). In fact, it has been shown that amnestic SCD (i.e., cognitive complaints referring to the memory domain) presents a brain atrophy pattern similar to that typically presented in Alzheimer’s disease (AD; Diaz-Galvan, Ferreira, et al, 2021 ). On the other hand, the same study showed that nonamnestic SCD seems to be associated with increased underlying small vessel disease in the general population ( Diaz-Galvan, Ferreira, et al, 2021 ).…”
mentioning
confidence: 99%